The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/w11030434
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Heterotrophic Nitrifying and Aerobic Denitrifying Arthrobacter nicotianae D51 Strain in the Presence of Copper

Abstract: A heterotrophic nitrification and aerobic denitrification bacterium, strain D51, was identified as Arthrobacter nicotianae based on morphological, phospholipid fatty acids (PLFAs), and 16S rRNA gene sequence analyses. Further tests demonstrated that strain D51 had the capability to use nitrite, nitrate, or ammonium as the sole nitrogen source in the presence of Cu2+. The maximum removal efficiencies of nitrite, nitrate and ammonium were 68.97%, 78.32%, and 98.70%, respectively. Additionally, the maximum growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…was observed in the presence of Cr 6+ stress (10 mgL −1 ) (Sun et al 2016). Similarly, Cu 2+ at a concentration > 0.1 mgL −1 inhibited growth and denitrification by Arthrobacter nicotianae (Cai et al 2019). Thus, strain ARB2 can be used in nitrate removal from wastewaters where salt and metal concentrations are low or within permissible limits.…”
Section: Time (H)mentioning
confidence: 95%
“…was observed in the presence of Cr 6+ stress (10 mgL −1 ) (Sun et al 2016). Similarly, Cu 2+ at a concentration > 0.1 mgL −1 inhibited growth and denitrification by Arthrobacter nicotianae (Cai et al 2019). Thus, strain ARB2 can be used in nitrate removal from wastewaters where salt and metal concentrations are low or within permissible limits.…”
Section: Time (H)mentioning
confidence: 95%
“…An increase in copper concentration from 0·01, to 0·1 mmol l −1 resulted in decreased denitrification from 99·8 to 16·3% (Lu et al ). A study conducted by Cai et al () showed the growth and denitrification ability of Arthrobater nicotianae in the presence of Cu 2+ . Cu 2+ at a concentration of >0·1 mg l −1 inhibited both growth and denitrification.…”
Section: Aerobic Denitrification In the Presence Of Metal Ionsmentioning
confidence: 99%
“…Many members of the genus Arthrobacter have been found to have the ability to reduce nitrate, such as Arthrobacter oryzae , Arthrobacter pokkalii , Arthrobacter globiformis , Arthrobacter arilaitensis ( Pinar and Ramos, 1997 ; Kageyama et al, 2008 ; He and Li, 2016 ; Krishnan et al, 2016 ). And it has been shown that the reduction of nitrate by Arthrobacter is usually considered to be through denitrification ( He et al, 2017 ; Zhong et al, 2018 ; Cai et al, 2019 ). However, nitrate reduction to ammonium by Arthrobacter has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%